2020
DOI: 10.1002/jcp.29787
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Toll‐like receptor 4 through anti‐miR‐Let‐7a enhances blastocyst attachment to endometrial cells in mice

Abstract: Despite encouraging advances in fertility technology, the success rate of an ongoing pregnancy is relatively low and predominantly associated with implantation failure. Inflammatory responses are beneficial in the fetomaternal interface and supposedly accelerate the chances for successful implantation. The current study aims to determine the effect of Toll‐like receptor 4 (TLR4) overexpression in mouse blastocysts via Let‐7a downregulation using intracytoplasmic sperm injection‐sperm‐mediated gene transfer on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…TLR4 enhances blastocyst attachment to endometrial cells in mice via miR-Let-7a suggested that inflammatory responses are beneficial in the fetomaternal interface and supposedly accelerate the chances for successful implantation. In our study, TLR1 was markedly up expression from oocyte to blastocyst development [40] . Therefore, the role of inflammatory responses is interesting need further study.GO and KEGG analyses of DEGs were then conducted.…”
Section: Discussionsupporting
confidence: 55%
“…TLR4 enhances blastocyst attachment to endometrial cells in mice via miR-Let-7a suggested that inflammatory responses are beneficial in the fetomaternal interface and supposedly accelerate the chances for successful implantation. In our study, TLR1 was markedly up expression from oocyte to blastocyst development [40] . Therefore, the role of inflammatory responses is interesting need further study.GO and KEGG analyses of DEGs were then conducted.…”
Section: Discussionsupporting
confidence: 55%
“…TLR4 enhances blastocyst attachment to endometrial cells in mice via miR-Let-7a suggesting that inflammatory responses are beneficial in the fetomaternal interface and supposedly accelerate the chances for successful implantation. In our study, TLR1 was markedly up expressed from oocyte to blastocyst development [ 39 ]. Therefore, the role of inflammatory responses is interesting and needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…[36] TNF-α interacts with NF-κB signaling pathway to participate in immune regulation, inflammatory response, and cell proliferation and differentiation, thus promoting the development of endometriosis. [37][38][39] The signaling pathways of cell proliferation, including MAPK and PI3K-AKT signaling pathways, promote the proliferation and migration of ectopic endometrial cells in patients with ectopia, and promote neoangiogenesis. [40]…”
Section: Genementioning
confidence: 99%